Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2514848620907470
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, entanglements, and (im)materialities: Reflections on the methods and methodologies of natural resource industries fieldwork

Abstract: This multi-authored collection of papers examines the complex realities of research on natural resource industries, including the messy entanglements of extraction, materiality, and everyday social life this research entails. Of central importance to the contributors is how scholars confront fieldwork challenges ethically, methodologically, and corporeally. The collection has two key objectives. First, it expands our understanding of extractive industry by bringing together work on resources conventionally und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 143 publications
(155 reference statements)
1
17
0
Order By: Relevance
“…As pointed out by Harris (2015), the theoretical basis of FPE is now well established, but "there is still considerable work to be done to continue extending and building FPE's analytical tools and frameworks" (xxi). This article's reflections echo the point that social identities like gender can cross-cut with other axes of difference to shape how a researcher gains access to populations, maintains rapport, and develops insights into the personal experiences of research subjects (Sultana 2007;Faria and Mollett 2016;Johnson et al 2020;McFarlane-Morris 2020). Even when research is conducted at "home," as shown in this article, some intersectional identities can still act as a distancing device, particularly if analysis is pitched at the household level or scaled further down to the human body.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…As pointed out by Harris (2015), the theoretical basis of FPE is now well established, but "there is still considerable work to be done to continue extending and building FPE's analytical tools and frameworks" (xxi). This article's reflections echo the point that social identities like gender can cross-cut with other axes of difference to shape how a researcher gains access to populations, maintains rapport, and develops insights into the personal experiences of research subjects (Sultana 2007;Faria and Mollett 2016;Johnson et al 2020;McFarlane-Morris 2020). Even when research is conducted at "home," as shown in this article, some intersectional identities can still act as a distancing device, particularly if analysis is pitched at the household level or scaled further down to the human body.…”
Section: Resultsmentioning
confidence: 82%
“…Indeed, these issues have rarely been singled out for critical analysis in FPE, notwithstanding the voluminous literature providing general overviews of this subfield (e.g., Rocheleau, Thomas-Slayter, and Wangari 1996;Mollett and Faria 2013;Elmhirst 2015). A few notable exceptions include Rocheleau (1995) and Johnson et al (2020). Feminist political ecologists need to spend more time thinking and reflecting critically about methodology, identity, and fieldwork relational quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations